The effect of an increased body mass index and obesity on the thickness of epicardial adipose tissue in men who underwent STEMI - I. N. Zakovryashina; L. A. Khaisheva; S. V. Shlyk; V. V. Shaposhnikova; A. D. Zakusilova (Медицинский вестник Юга России, 2024)
Objective: to assess the thickness of epicardial adipose tissue in patients of different BMI, to establish relationships with the lipid profile during 48 months of observation.Materials and methods: 121 men were selected for an open prospective study. Three main groups were identified: group 1 — 24 patients with normal BMI (20%), group 2 — 35 men with excess BMI (29%), group 3 — 62 obese patients (51%). The control group (4) included 27 practically healthy men. Three stages of prospective observation of patients were determined: at the time of hospitalization, 12 and 48 months (±2 weeks) from the index event.Results: EAT thickness measured by echocardiography in patients with STEMI correlated with BMI, waist circumference (WC) throughout of the entire study, the strength of the connection was significantly higher with OT. EAT thickness in patients with STEMI increased in the over-BMI and obesity groups from the beginning to the end of the study (p <0.05) and was statistically significantly higher than in the control group and in patients with normal BMI. Throughout the study, eVT had a weak positive correlation with the level of blood triglycerides, total cholesterol and LDL-C.Conclusions: the thickness of epicardial adipose tissue correlates with waist circumference and atherogenic indicators of lipid metabolism.